Magnetic Resonance Imaging of Cerebrospinal Fluid Spread in the Epidural Space and Postdural Puncture Headache in Obstetrics: A Proof-of-Concept Study. Issue 2 (24th June 2022) - Ahmed, I.; Majeed, A.; Fernando, R.; Hyare, H.; Columb, M.; Setty, T.
Abstract : ( Eur J Anaesthesiol . 2021;38:777–784) Labor analgesia that includes epidural catheter placement can be complicated by accidental dural puncture (ADP). In parturients, ADP is followed by postdural puncture headache (PDPH) in up to 70% to 80% of cases. Prompt diagnosis and treatment of PDPH are important as delay can exacerbate sequelae, leading to serious debilitating and chronic complications. The current most effective treatment, epidural blood patch (EBP), is performed based on subjective clinical judgment of the parturient's progression and severity of symptoms. An evidence-based protocol may benefit parturients with atypical PDPH presentation by allowing an earlier EBP, rather than forestalling until PDPH becomes severe. Egress of cerebrospinal fluid (CSF) into the epidural space following ADP can be readily recognized in T1-weighted and T2-weighted magnetic resonance imaging (MRI) of the brain and spine. The correlations between neuroradiological findings and the severity of PDPH in obstetric patients is presented.